Surface Stability in Drylands Is Influenced by Dispersal Strategy of Soil Bacteria. Issue 11 (15th November 2019) - Elliott, David R.; Thomas, Andrew D.; Strong, Craig L.; Bullard, Joanna
Abstract: Microbial adaptations for survival and dispersal may directly influence landscape stability and potential for dust emission in drylands where biological soil crusts (biocrusts) protect mineral soil surfaces from wind erosion. In the Lake Eyre basin of central Australia we operated a wind tunnel on sandy soils and collected the liberated material, which was subjected to DNA sequencing to identify the microbial community composition. Microbial composition of entrained dust was compared with that of the source sand dune soil in addition to nearby claypan and nebkha soils and water channels that together form a recycling sediment transport system. Wind was found to preferentially liberate 359 identified taxa from sand dunes, whereas 137 identified taxa were found to resist wind erosion. Water channel communities included many taxa in common with the soil samples. We hypothesize that the ease with which soil microbes become airborne is often linked to whether the organism is adapted for dispersal by wind or vegetative growth and that biocrust organisms found in water channels may sometimes use a fluvial dispersal strategy, which exploits rare flooding events to rapidly colonize vast pans that are common in drylands. We explain likely geomorphic implications of microbial dispersal strategies which are a consequence of organisms engineering the environment to provide their particular needs. By identifying microbes fitting expectations for these dispersal strategies based on differential abundance analyses, we provide a new perspective for understanding the role of microbiota in landscape stability. Key Points: Microbial communities of dryland ephemeral lake bed, dunes, and river channels are characterized Wind preferentially mobilizes specific microbes from soil surface biocrusts Microbial dispersal adaptations may influence soil stability by promoting or inhibiting adhesion